Absence of an effect of high nitrate intake from beetroot juice on blood pressure in treated hypertensive individuals: A randomized controlled trial - Bondonno, C.; Liu, A.; Croft, K.; Ward, Natalie; Shinde, S.; Moodley, Y.; Lundberg, J.; Puddey, I.; Woodman, R.; Hodgson, J. (2015)
Background: Dietary nitrate, which is in green leafy vegetables and beetroot, decreases blood pressure through the enterosalivary nitrate-nitrite-nitric oxide pathway in healthy individuals. Whether similar effects would occur in individuals with treated hypertension and, therefore, at increased risk of cardiovascular disease is unclear. Objective: We assessed whether increased dietary nitrate intake by using beetroot juice for 1 wk lowers blood pressure in treated hypertensive men and women. Design: Participants (n = 27) were recruited to a randomized, placebo-controlled, double-blind crossover trial. The effect of 1-wk intake of nitrate-rich beetroot juice was compared with 1-wk intake of nitrate-depleted beetroot juice (placebo). The primary outcome was blood pressure assessed by measuring home blood pressure during the intervention and 24-h ambulatory blood pressure on day 7 of the intervention. Other outcomes included nitrate metabolism assessed by measuring nitrate and nitrite in plasma, saliva, and urine. Results: Relative to the placebo, 1-wk intake of nitrate-rich beetroot juice resulted in a 3-fold increase in plasma nitrite and nitrate, a 7-fold increase in salivary nitrite, an 8-fold higher salivary nitrate, and a 4-fold increase in both urinary nitrite and nitrate (P < 0.001). However, no differences in home blood pressure and 24-h ambulatory blood pressure were observed with 1-wk intake of nitrate-rich beetroot juice in comparison with the placebo. Conclusion: An increase in dietary nitrate intake may not be an effective short-term approach to further lower blood pressure in treated hypertensive subjects.